Altitude training at home
The high-tech, cutting-edge Hypoxic Tent SystemTM (developed and patented by Hypoxico Inc., New York) provides a low-oxygen (hypoxic) environment for resting or sleeping at standard atmospheric pressure. The HTS is a suitcase-sized, portable system, which includes a hypoxic generator and a lightweight tent, that can be set up over any bed, at home or on the road. The hypoxic generator continuously supplies air with oxygen content of 14.5% simulating inside the tent the "altitude" of 9,000 feet (2700m). Special systems adjustable to higher altitudes can be provided for top athletes. Using HTS for 6-8 hours a day is sufficient to stimulate "altitude" acclimatization resulting in increased Red Blood Cell production, Vo2 max and greater aerobic performance. Hypoxic Tent System is available in 120V/60Hz and 220/240V/50Hz Models.